Metapolitics from Wagner and the German Romantics to Hitler - Viereck, Peter (New Brunswick, NJ [u.a.] : Transaction Publ., 2004)
"The term "metapolitics," a coinage from Richard Wagner's nationalist circle, signifies an ideology resulting from five distinct strands: romanticism (embodied chiefly in the Wagnerian ethos), the pseudo-science of race, Fuehrer worship, vague economic socialism, and the alleged supernatural and unconscious force of the Volk collectivity. Together, those elements engendered an emphasis on irrationalism and hysteria and belief in a special German mission to direct the course of the world's history." "Viereck analyzes nineteenth-century German thought's conflicting attitudes toward political procedures and social arrangements rooted in classical, rational legalistic, and Christian traditions. This edition includes an appreciation by Thomas Mann and an exchange with Jacques Barzun debating Viereck's criticism of German romanticism. Viereck's essays on the case of Albert Speer, on Claus von Stauffenberg (the German officer who led the army conspiracy to assassinate-Hitler), and on the poets Stefan George and Georg Heym appear here for the first time in book form."--BOOK JACKET.
A-10